Analysis of Electrical Circuits with Variable Load Regime Parameters: Projective Geometry Method - Penin, A (Springer, 2016)
This book introduces electric circuits with variable loads and voltage regulators. It allows to define invariant relationships for various parameters of regime and circuit sections and to prove the concepts characterizing these circuits. Generalized equivalent circuits are introduced. Projective geometry is used for the interpretation of changes of operating regime parameters. Expressions of normalized regime parameters and their changes are presented. Convenient formulas for the calculation of currents are given. Parallel voltage sources and the cascade connection of multi-port networks are described. The two-value voltage regulation characteristics of loads with limited power of voltage source is considered. The book presents the fundamentals of electric circuits and develops circuit theorems. It is useful to engineers, researchers and graduate students who are interested in the basic electric circuit theory and the regulation and monitoring of power supply systems.